2016
DOI: 10.1039/c6ra07760a
|View full text |Cite
|
Sign up to set email alerts
|

Spectroscopic and microscopic investigation of the effects of bacteria on dental implant surfaces

Abstract: The surface morphology and chemical composition of commercially pure titanium dental implants and healing abutments exposed in vitro or in vivo to oral bacteria were studied.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
26
1
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 28 publications
(31 citation statements)
references
References 53 publications
3
26
1
1
Order By: Relevance
“…Additionally, the accumulation of organic acids in these regions, creates localized, acidic environments which promote corrosion features including discoloration and pitting . In our previous study, both early‐colonizing S. mutans and late‐colonizing Porphyromonas gingivalis induced corrosion of Ti‐SLA implants after 30‐day immersion periods in vitro . Additionally, analysis of failed Ti dental implant retrievals demonstrated signs of severe corrosion attack including pitting, surface discoloration, and increased surface roughness .…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…Additionally, the accumulation of organic acids in these regions, creates localized, acidic environments which promote corrosion features including discoloration and pitting . In our previous study, both early‐colonizing S. mutans and late‐colonizing Porphyromonas gingivalis induced corrosion of Ti‐SLA implants after 30‐day immersion periods in vitro . Additionally, analysis of failed Ti dental implant retrievals demonstrated signs of severe corrosion attack including pitting, surface discoloration, and increased surface roughness .…”
Section: Discussionsupporting
confidence: 87%
“…Post‐immersion, all metallic implants – Ti‐SLA, Ti‐modSLA, and TiZr‐SLA – exhibited surface discoloration to an extent which can be attributed to corrosion induced by exposure to bacteria (Figures and and supplementary Figs. through 3 in online Journal of Periodontology ) as demonstrated in previous studies for Ti‐based implants . On the other hand, only minimal surface changes were observed to occur on ZrO 2 ‐SLA implants (Figure and supplementary Fig.…”
Section: Discussionsupporting
confidence: 66%
“…The prevalence of metallic titanium (Ti 0 ) on non‐anodized samples compared anodized samples after sputtering indicate that the anodized surface had a thicker oxide layer. These findings are supported by a previous study investigating retrieved failed implants for early signs of corrosion reported similar XPS results on anodized and non‐anodized titanium …”
Section: Discussionmentioning
confidence: 99%
“…One of the main causes of biologically based implant failures is infiltration of bacteria in the peri‐implant pocket, which allows the formation of a bacterial biofilm on implant surfaces . This biofilm can induce inflammation in adjacent tissues and disrupt osseointegration, resulting in peri‐implant mucositis or peri‐implantitis . In addition, metabolic byproducts of anaerobic bacteria such as S. Mutans , can locally lower the pH of the fluid surrounding the peri implant pocket or contacting surfaces of the peri implant mucosa .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation